Radial constraints on the initial mass function from TiO features and wing-ford band in early-type galaxies$Francesco La Barbera, Alexandre Vazdekis, Ignacio Ferreras, Anna Pasquali, Michele Cappellari, Ignacio Martin-Navarro, Frederik Schönebeck, Jeśus Falćon-Barroso - La Barbera, Francesco; Pasquali, Anna; Schönebeck, Frederik (Arxiv, 2015)
At present, the main challenge to the interpretation of variations in gravity-sensitive line strengths as driven by a non-universal initial mass function (IMF), lies in understanding the effect of other parameters describing unresolved stellar populations, such as elemental abundance ratios. We combine various TiO-based, IMF-sensitive indicators in the optical and NIR spectral windows, along with the FeH-based Wing-Ford band to break this degeneracy. We obtain a significant radial trend of the IMF slope in XSG1, a massive early-type galaxy (ETG), with velocity dispersion sigma~300km/s, observed with the VLT/X-SHOOTER instrument. In addition, we constrain both the shape and normalization of the IMF based only on a stellar population analysis. We robustly rule out a single power-law to describe the IMF, whereas a power law tapered off to a constant value at low masses (defined as a bimodal IMF) is consistent with all the observational spectroscopic data and with the stellar M/L constraints based on the Jeans Anisotropic Modelling method. The IMF in XSG1 is bottom-heavy in the central regions (corresponding to a bimodal IMF slope Gb~3, or a mass normalization mismatch parameter alpha~2), changing towards a standard Milky-Way like IMF (Gb~1.3; alpha~1) around half of the effective radius. This result, combined with previous observations of local IMF variations in massive ETGs, reflects the varying processes underlying the formation of this type of galaxies, between the central core and the outer regions.